PENGARUH METODE MIND MAPPING TERHADAP KEMAMPUAN MENULIS KARANGAN NARASI SISWA SEKOLAH DASAR - Izza Mauli Avrianty; Ahmad Nurefendi Fradana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is based on the problem of low writing ability for students. Writing skills involve learners in improving the correct use of vocabulary, spelling, and language structure. Writing skills that can be improved are the ability to write narrative essays. Currently, the ability to write for students has obstacles that require teachers to use methods that can make it easier for students to compose narrative texts. The method applied to this research is the mind mapping method as an alternative to overcoming writing barriers. This research aims to recognise the effectiveness of the mind mapping method to write narrative essays in Indonesian language subjects. The method used in this research is quantitative. The subjects in this research are students of grade V Elementary School. The data collection technique used is a narrative writing skill test. The results of the T-test in this study obtained a sig value. (2-tailled) of 0.00 < 0.05 then H0 was rejected and H1 was accepted which means that there was a significant influence. It can be concluded that there is an influence on the use of the mind mapping method on improving the writing of narrative essays for students in grade V of elementary school.